Short-Chain Fatty Acids Calibrate RARα Activity Regulating Food Sensitization - Yuan, Xiefang; Tang, Hongmei; Wu, Renlan; Li, Xingjie; Jiang, Hongyu; Liu, Zhigang; Zhang, Zongde (Frontiers in Immunology, 2021)
Gut-microbiota dysbiosis links to allergic diseases. The mechanism of the exacerbation of food allergy caused by gut-microbiota dysbiosis remains unknown. Regulation of retinoic acid receptor alpha (RARα) signaling is critical for gut immune homeostasis. Here we clarified that RARα in dendritic cells (DCs) promotes Th2 cell differentiation. Dysbiosis stimulates retinoic acid signaling in mucosal DCs. We found microbiota metabolites short-chain fatty acids (SCFAs) maintain IGF-1 levels in serum and mesenteric lymph nodes. The IGF-1/Akt pathway is essential for regulating the transcription of genes targeted by RARα. And RARα in DCs affects type I interferon (IFN-I) responses through regulating transcription of IFN-α. Our study identifies SCFAs crosstalk with RARα in dendritic cells as a critical modulator that plays a core role in promoting Th2 cells differentiation at a state of gut dysbiosis.